E-Bayesian and hierarchical Bayesian estimations for the system reliability parameter based on asymmetric loss function. Issue 1 (2nd January 2017) - Yousefzadeh, F.
ABSTRACT: This paper explores properties of the E-Bayesian and hierarchical Bayesian estimations of the system reliability parameter. E-Bayesian estimation and hierarchical Bayesian estimation of Pascal distribution's parameter under two loss function, LINEX loss function and entropy loss function can be found. We obtained limits of that the E-Bayesian estimation and hierarchical Bayesian estimation are equal. A Monte Carlo simulation is used to compare performances of the two methods.